Kepemimpinan Kristiani dalam Terang Bonum Commune: Relevansi Pemikiran Thomas Aquinas di Era Kontemporer - Aluysius Hendra Wijaya; Laurentius Prasetyo (Jurnal Filsafat dan Teologi Katolik, 2026)
This article explores the relevance of Thomas Aquinas’ concept of bonum commune (the common good) in shaping a Christian leadership paradigm amid the global and national leadership crisis, particularly in Indonesia. The phenomena of corruption, abuse of power, and weak moral orientation indicate the absence of the common good as the guiding principle in contemporary political practices. Employing a qualitative library research method, this study analyzes Aquinas’ thought, the Scriptures, Catholic social teaching, and modern literature on theology and political philosophy. The findings reveal that bonum commune serves as a fundamental principle that integrates moral, spiritual, and social dimensions of leadership. Within the Christian perspective, the principles of service, justice, love, and participation find their philosophical and theological foundation, with Jesus Christ as the Good Shepherd as their ultimate model. This article emphasizes that Christian leadership rooted in bonum commune is not about domination but about servant leadership oriented toward the common good, social justice, and human dignity. A reinterpretation of Aquinas’ thought in the modern context highlights the need to understand bonum commune through dialogue, participation, and respect for pluralism. Therefore, Christian leadership in the light of bonum commune remains relevant as an alternative paradigm for building a more just, transparent, participatory, and humane society